Theoretical foundations of the problem of harmonization of intellectual and emotional aspects of learning - Максименко, І. Г.; Шепеленко, Т. Л. (Pedagogy of Higher and Secondary Education, 2011)
In the article the necessity of harmonization of intellectual and emotional factors is grounded as to the mean of increase of effectiveness of educational process.